2021
DOI: 10.1101/2021.05.22.21257658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of COVID-19 vaccines against the B.1.617.2 variant

Abstract: Background: The B.1.617.2 COVID-19 variant has contributed to the surge in cases in India and has now been detected across the globe, including a notable increase in cases in the UK. We estimate the effectiveness of the BNT162b2 and ChAdOx1 COVID-19 vaccines against this variant. Methods: A test negative case control design was used to estimate the effectiveness of vaccination against symptomatic disease with both variants over the period that B.1.617.2 began circulating with cases identified based on seque… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
185
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(199 citation statements)
references
References 24 publications
7
185
2
5
Order By: Relevance
“…(2.7-3.8-fold) [191,192] Vaccine efficacy slightly lower or unchanged, largely preserved neutralizing titers 1. BNT162b2: 89.5-93.4% [200,217] 2. NVX-CoV2373: 86% [222].…”
Section: Sars-cov-2 Variantsmentioning
confidence: 99%
See 3 more Smart Citations
“…(2.7-3.8-fold) [191,192] Vaccine efficacy slightly lower or unchanged, largely preserved neutralizing titers 1. BNT162b2: 89.5-93.4% [200,217] 2. NVX-CoV2373: 86% [222].…”
Section: Sars-cov-2 Variantsmentioning
confidence: 99%
“…2. Partially evaded neutralization by the antibodies induced through natural infection [214,217] 1. BNT162b2 vaccine: 90% [217].…”
Section: Sars-cov-2 Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies have shown a significant reduction in the neutralization against B.1.617 lineage variants by antibodies received from natural infections and manycurrently used COVID-19 vaccines and multiple monoclonal antibodies (5)(6)(7)(8). Higher transmissibility and immunoescape is being reported for B.1.617.2, which is currently the fastest growing SARS-CoV-2 strain in the Indian population (1,(9)(10). Until December 2020, B.1.1.7 was a dominant strain in the Indian population, although the first cases of B.1.617 lineage had started appearing by then.…”
mentioning
confidence: 99%